Republic of Yemen - Joint Social and Economic Assessment - World Bank (Washington, DC, 2013)
This Joint Social and Economic Assessment (JSEA) has been prepared in response to a request from the Ministry of Planning and International Cooperation (MoPIC), and was undertaken jointly by the World Bank, the United Nations, the European Union, and the Islamic Development Bank. The JSEA's main purpose is to assess the social and economic impact of the crisis in Yemen, and to identify challenges and key priorities for early interventions, primarily for the transition period, which is expected to stretch into the first half of 2014. Putting Yemen on a path of recovery to prosperity will not only require a strong commitment and ownership from the Government and People of Yemen, but also coordinated support and significant financial resources from all partners and friends of Yemen. While the JSEA provides analysis of Yemen's most pressing needs, it is the Government's Transition Plan that will offer the roadmap by which Yemen can emerge from crisis stronger and better able to ensure equitable and sustainable development for its people. The implementation of the Transition Plan and donor support should balance humanitarian assistance, early recovery, reconciliation, and peace-building efforts in the short run, with support to decisive policy actions and reforms that will underpin sustainable and inclusive development, improved governance, and social protection in the medium to long term.